Preparation of cation-exchange membrane chromatography by modification of polyamide membrane through grafting of methacrylic acid monomer - Nurul Alia, Khalil (2012)
Nowadays,with the increase demand of protein production and purity,the purification cost of the protein also increases about 50 to 90%. Packed bed chromatography is widely used in protein separation.However,there are some limitations of the packed bed chromatography such as high-pressure drop, channeling problem and complicated scale up process.Most of these limitations can be overcome by membrane chromatography.The main objective of this research is to prepare cation-exchange membrane chromatography from polyamide membrane by chemical grafting of methacrylic acid monomer.Potassium persulfate and potassium metabisulfite was used to generate the radicals in the polyamide membrane and grafted with methacrylic acid monomer together with ethylene glycol dimethacrylate as a cross-linker.Different monomer concentration between 0.1 and 1.0M and monomer grafting duration from 15 – 120 min was studied toward producing high protein binding capacity membrane.Optimum time for grafting methacrylic acid onto polyamide membrane was 45 minutes with the binding capacity 599.6390 mg/g BSA at the monomer concentration of 0.1 M.Identification and optimization of critical parameter in grafting process is crucial for the development of high performance membrane chromatography materials.